Are Workers' Enterprises entry policies conventional? - Michele Moretto; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
One of the main reasons why workers' enterprises (WE) still represent a relevant chunk of the economy may lay in some affinities with conventional profit maximizing firms. To prove this, we compare the entry policies of WEs and conventional firms when they can decide size at entry while having to stick to it afterwards. Even though short run differences remain, a long run coincidence appears besides that under certainty. Endogenizing size and time of entry in an uncertain dynamic environment we see that WEs enter at the same trigger and size of conventional firms. Both of them wait less and choose a dimension larger than the minimum efficient scale. This may be another way to explain why WE are still an important share of the economy (Hesse and Cihàk, 2007) despite the ongoing mantra of their imminent demise.
Keywords: 330